Balloon angioplasty for supravalvular aortic stenosis as an early complication following arterial switch operation - Kaitlin Carr; Osamah Aldoss; Bijoy Thattaliyath; Manish Bansal (Wolters Kluwer Medknow Publications, 2018)
Supravalvular aortic stenosis as an early complication of transposition of the great artery repair is rare with few cases reported. Furthermore, transcatheter intervention is uncommon as surgical re-intervention has been traditionally done. We describe two cases of supravalvular aortic stenosis at the anastomotic site as an early complication of the arterial switch operation. Both patients underwent balloon angioplasty of the supravalvular aorta with improvement in postangioplasty gradients and angiographic appearance. Both patients at short-term follow-up had persistent improved gradient without need for further intervention.